PERANCANGAN APLIKASI SISTEM PENDUKUN KEPUTUSAN PEMILIHAN JENIS BIBIT CENGKEH BERKUALITAS UNGGUL MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) BERBASIS WEB - Nisrawati (LPPM STMIK BINA ADINATA, 2020)
Research aims to: (1) Designing the Decision support system of selection of clove seed type of superior quality with the method of analytic hierarchy Process (AHP) Web-based, (2) Implementing a decision support system in the selection of seeds of superior clove plants using the Web-based AHP method. The research methodology used is the waterfall method of a software development model that provides a sequential or sequential approach to the flow of the software from analysis, design, coding, testing, verification and maintenance and the method of SPK AHP which is a method that compares direct decision making with human perception by decision making using AHP method in which the method includes numeric value in lieu of human perception in comparison relative to the end with a conclusion which element has a value of priority Highest.The data used is primary data and secondary data collected by observing directly the research site, interviews with interviewees related to the library by studying books and journals related to cloves. Results of the decision-making system of superior quality clove seed selection using the Web based AHP method: (1) Help the farmers to choose the best type of seeds and (2) know the information criteria of clove seedlings of the seed to increase productivity and the quality of the results of Clove Plantation.